Age and sex differences in game-related statistics which discriminate winners from losers in elite basketball games - Haruhiko Madarame (Universidade Estadual Paulista (UNESP), 2018)
Abstract AIMS To advance knowledge of long-term development of basketball players, this study investigated age and sex differences in game-related statistics which discriminate winners from losers in World Basketball Championships held after the 2010 rule change. METHODS A total of 935 games from six categories (under-17, under-19 and open age for both men and women) were analyzed. All games were classified into three types (balanced, unbalanced and very unbalanced) according to point differential by a k-means cluster analysis. A discriminant analysis was performed to identify game-related statistics which discriminate winners from losers in each game type. An absolute value of a structural coefficient (SC) equal to or above 0.30 was considered relevant for the discrimination. RESULTS In balanced games, assists discriminated winners from losers in open games (men, |SC| = 0.32; women, |SC| = 0.34), whereas successful free throws did so in under-17 games (men, |SC| = 0.30; women, |SC| = 0.31). Successful 2-point field goals discriminated winners from losers only in women's games (under-19, |SC| = 0.38; open, |SC| = 0.36). CONCLUSION There were three novel findings in balanced games: 1) successful free throws but not assists discriminated winners from losers in under-17 games; 2) successful 2-point field goals discriminated winners from losers in women's games but not in men's games; and 3) discriminating power of successful 3-point field goals was extremely small in women's games. These results may be related to the new rules for the shot clock and the 3-point distance.